Atherosclerotic Extension of Carotid Arteries: An Insertion in Clinical Practice - M. L. Furlanetto; E. F. B. Chagas; Payão SLM (International Journal of Vascular Medicine)
Introduction. Atherosclerotic disease is a diffuse disease that is strongly associated with age, risk factors, and variable progression. The anatomical prevalence of atheromas does not always follow, a sequence by sectors, and in many cases are concomitant. Objectives. This study is aimed at studying atherosclerosis in the arterial territories of the carotid and lower limbs, in order to correlate their extension as a form of primary prevention. Methods. Participating patients with the main risk factors for atherosclerotic disease were composed of two groups: one with chronic peripheral obstructive arterial disease (PAD) and another without PAD. After performing carotid ultrasound Doppler (USD) of all patients, the occasional prevalence of the disease was evaluated. We performed by statistical tests the correlation between the findings in these patients and the risk factors. Obtaining n from 226 patients, in which 116 patients are from the PAD group and 110 patients are from the group without PAD. Results. Our findings add up to 8.8% for lesions over 50% in patients with PAD, with 6.2% over 70% meeting the few published scientific findings. In this study, the correlation was evaluated between carotid stenosis and PAD, in which we observed a positive association. We observed in the studies that the prevalence of moderate and severe carotid stenosis was similar to patients with coronary artery disease (CAD). There are a number of nonclassical risk factors that we do not evaluate, but even studying the traditional ones, we find that they are less than 27% dependent. Conclusion. Therefore, our study proposes an improvement in the clinical approach of patients with PAD for both the carotid and coronary territory, not using only 2 factors traditional risk factors, for the extension study and to consider the PAD that has 10% dependence alone, as effect and projection of the carotid atherosclerotic plaque.